Variability in carbon uptake and (re)cycling in Antarctic cryptoendolithic microbial ecosystems demonstrated through radiocarbon analysis of organic biomarkers. Issue 1 (26th October 2017) - Brady, A. L.; Goordial, J.; Sun, H. J.; Whyte, L. G.; Slater, G. F.
Abstract: Cryptoendolithic lichens and cyanobacteria living in porous sandstone in the high‐elevation McMurdo Dry Valleys are purported to be among the slowest growing organisms on Earth with cycles of death and regrowth on the order of 10 3 –10 4 years. Here, organic biomarker and radiocarbon analysis were used to better constrain ages and carbon sources of cryptoendoliths in University Valley (UV; 1, 800 m.a.s.l) and neighboring Farnell Valley (FV; 1, 700 m.a.s.l). Δ 14 C was measured for membrane component phospholipid fatty acids (PLFA) and glycolipid fatty acids, as well as for total organic carbon (TOC). PLFA concentrations indicated viable cells comprised a minor (<0.5%) component of TOC. TOC Δ 14 C values ranged from −272‰ to −185‰ equivalent to calibrated ages of 1, 100–2, 550 years old. These ages may be the result of fractional preservation of biogenic carbon and/or sudden large‐scale community death and extended period(s) of inactivity prior to slow recolonization and incorporation of 14 C‐depleted fossil material. PLFA Δ 14 C values were generally more modern than the corresponding TOC and varied widely between sites; the FV PLFA Δ 14 C value (+40‰) was consistent with modern atmospheric CO2, while UV values ranged from −199‰ to −79‰ (calibrated ages of 1, 665–610 years). The observed variability in PLFA Δ 14 C depletions is hypothesized to reflect variations in the extent of fixation of modern atmospheric CO2 and the preservation and recycling of older organic carbon by the community in various stages of sandstone recolonization. PLFA profiles and microbial community compositions as determined by molecular genetic characterizations and microscopy differed between the two valleys (e.g., predominance of biomarker 18:2 [>50%] in FV compared to UV), representing microbial communities that may reflect distinct stages of sandstone recolonization and/or environmental conditions. It is thus proposed that Dry Valley cryptoendolithic microbial communities are faster growing than previously estimated.